Integrating end-user feedback in the concept stage of development of a novel sensor access system for environmental control. (19th May 2018) - Fager, Susan Koch; Sorenson, Tabatha; Butte, Susanne; Nelson, Alexander; Banerjee, Nilanjan; Robucci, Ryan
Abstract: Purpose: This article illustrates user-centred design of a novel sensor access system for environmental control in the concept stage of development. Methods: Focus groups of individuals with disabilities and rehabilitation healthcare professionals were provided with video illustration of the technology and asked to provide quantitative and qualitative feedback through a semistructured interview process. Qualitative methods were employed to analyse transcribed comments to develop themes supporting ongoing development of the technology. Results: Both end-user streams rated the original design features of the sensor access system (alternative interface to assistive technologies, having wireless capabilities and not requiring batteries) as having high potential value. Both groups identified a need for the future design of the sensor technology to be able to capture minimal/reduced movements for those with severe physical impairments. Themes included (1) the sensor technology could be individualized/customized to accommodate the user, (2) minimal positioning and set-up requirement and (3) technology that alleviated problems encountered with touch-based solutions. Conclusions: Inclusion of end-user feedback provided the research team with valuable information that supported the initial conceptualization of the design features of the technology and provided valuable data to support development of a new prototype that can capture more reduced/minimal movements. Implication for Rehabilitation: User-centered design of assistive technology is essential to the development of technology that can meet the unique needs of those with the most severe physical impairments. New sensor technology may alleviate some of the access challenges faced by individuals with severe physical impairments. Collaboration between all key stakeholders (individuals with disabilities, rehabilitation professionals, researchers, and developers) is an essential component in the iterative assistive technology design process.